SYNTHESIS OF 2-METHOXY-4,6-DI(PROP-1-ENYL)PHENOL FROM EUGENOL AND ITS ACTIVITY AS AN ANTIOXIDANT - Hernawan Hernawan; Bambang Purwono; Tutik Dwi Wahyuningsih (Indonesian Journal of Chemistry, 2012)
Synthesis and antioxidant activity of 2-methoxy-4,6-di(prop-1-enyl) phenol from eugenol have been investigated. Synthesis was conducted through three stages of reaction. The first step was CTAB micellar catalytic O-allylation reaction at room temperature, to give 4-allyl-1-(allyloxy)-2-methoxybenzene (2). Compound (2) was subsequently heated for Claisen rearrangement and produced 2,4-diallyl-6- methoxyphenol (3). The final steps was isomerization of compound (3) in alkaline conditions in ethylene glycol, to yield 2-methoxy-4,6-di(prop-1-enyl) phenol (4). Antioxidant activity test was conducted by TBARS and DPPH methods. TBARS test showed that the compound (4) at a concentration of 50 μM could inhibit the oxidation of linoleic acid shown by the increasing of time lag phase (96 ± 2.94 min), reducing the rate of propagation (± 54.54%) and reducing of malonal dialdehyde (MDA) formation (68.04 ± 0.84%). The DPPH test revealed that compound (4) indicated DPPH free radical scavenging activity with IC50 107.66 μM and comparable with IC50 for BHT 107.37 μM.